2020
DOI: 10.17221/63/2019-pps
|View full text |Cite
|
Sign up to set email alerts
|

Arthropod pests of pistachios, their natural enemies and management

Abstract: Commercial pistachio cultivation and production began about a century ago in Iran. The size of this industry has gradually increased and the pistachio nut production in Iran is now the largest worldwide, although it has declined over last few years due to long periods of harsh drought, the mismanagement of water resources and the impact of climate change. Research on pests and diseases was started in the 1940s due to the demands of the growers who were facing economic damage by herbivorous insects. Much resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 65 publications
0
22
0
2
Order By: Relevance
“…Pistachio nuts, Pistacia vera L., comprise one of the most important and valuable crops cultivated in Mediterranean countries (Greece, Turkey, Spain, Italy, and Tunisia), the Middle East (Syria and Iran), Australia and the southwestern United States (Arizona and California) (Kaska 1994;Sheibani 1995;Ferguson 2016). Pistachios are the major agricultural product in the tropical regions of Iran, especially in Rafsanjan, Kerman Province, which is the country's main pistachio producing area (Mehrnejad 2020). Pistachio is one of the most important export products in Iran and plays a key role in the agricultural economy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pistachio nuts, Pistacia vera L., comprise one of the most important and valuable crops cultivated in Mediterranean countries (Greece, Turkey, Spain, Italy, and Tunisia), the Middle East (Syria and Iran), Australia and the southwestern United States (Arizona and California) (Kaska 1994;Sheibani 1995;Ferguson 2016). Pistachios are the major agricultural product in the tropical regions of Iran, especially in Rafsanjan, Kerman Province, which is the country's main pistachio producing area (Mehrnejad 2020). Pistachio is one of the most important export products in Iran and plays a key role in the agricultural economy.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of various pests is an important factor that can reduce yield in Iran's pistachio orchards and is much more significant than other harmful biotic factors, such as nematodes and fungal and bacterial pathogens. Many phytophagous Hemiptera in the families Pentatomidae, Miridae and Lygaeidae are considered worldwide pistachio pests and can cause remarkable damage to the fruits during the growing season (Mehrnejad 2020). Based on previous studies, pentatomid stink bugs are a key pest group and ranked as the second most important pests in pistachio orchards (Mehrnejad et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…pathogen, Nematospora coryli Peglion, a pathogen of pistachio nuts (Pourkhatoon et al, 2016). This group of stink bugs includes the species Acrosternum arabicum Wagner, Acrosternum heegeri Fieber, Acrosternum millieri Mulsant & Rey, Apodiphus amygdali Germar, Brachynema germari Kolenati, and Brachynema segetum Jakovlev (Kashkouli et al, 2019a;Mehrnejad, 2020). Most of information concerning the associations with gut primary symbionts regards B. germari and Acrosternum spp., in consideration of their primary importance as pests (Kashkouli et al, 2019a).…”
Section: Pistachio Green Stink Bugsmentioning
confidence: 99%
“…This family encompasses a number of agricultural pests that are responsible for huge economic losses worldwide, as they feed on a variety of fruits and seeds, seriously affecting crop yield and quality (Conti et al, 2020). Heavy attacks are recorded on almost all economically relevant crops, including commodity crops such as cotton, rice, maize, soybean, and wheat (Leskey and Nielsen, 2018;Zerbino and Panizzi, 2019;Defensor et al, 2020;Sosa-Gómez et al, 2020), fruit trees (Leskey and Nielsen, 2018;Mi et al, 2020;Powell, 2020), nuts (Bosco et al, 2018;Mehrnejad, 2020), and vegetables (Palumbo et al, 2016;Leskey and Nielsen, 2018). Furthermore, the invasive potential of many pentatomid species, such as Halyomorpha halys (Stål), Nezara viridula L., Erthesina fullo Thunberg, or Bagrada hilaris (Burmeister), makes them major agricultural threats in several areas outside their native range (Palumbo et al, 2016;Leskey and Nielsen, 2018;Conti et al, 2020;Mi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…reported that O. conglobata is one of the important natural enemies of insect pests in pistachio orchards Mehrnejad (2020). reported that Polydrosus davatchii Hoffman, Hippodamia variegata Goeze, Scymnus spp.…”
mentioning
confidence: 99%